Effects of Video Display Terminal Resolutions to the Legibility of Text on a Web Page - Ahmad Affendi, Hashim; Mazlina, Abdul Majid (Penerbit UMP, 2015)
Higher Video Display Terminal (VDT) resolutions have been proven to provide better quality in improving image quality displayed. The higher the resolution means more pixels per-inch-square available to display an image. This increase, however, may not be to the fonts used on web pages for improved legibility. Legibility of web text has been proved essential to ensure the quality of a web page. Support by the evidence from the previous research experiment results; low level of web text legibility can cause various visual related problems and usability of a web page. This research will focus on finding possible improvement effects on VDT resolution that might need to be considered in designing the web text. In this research 6 font types and two VDT resolutions for low and high have been selected. Approximately 200 subjects were randomly selected for this experiment. The selected subjects were divided into two groups for low and high resolution. Selected subjects performed legibility test and subjective preference test experiments on 6 selected type of fonts. Overall findings indicate that there is an improvement but no significant difference between the two VDT resolutions.